The Influence of Social Media Influencers and Emotional Value on Purchasing Decisions for Virtual Items in Valorant Online Game - M. Sultan Arda; Hilmiati Fauzi; M. Ilhamuddin (Tinta Emas Institute, 2023)
This study aims to determine the effect of social media influencers and emotional value on virtual iten purchasing decisions in the valorant online game. This study uses a quantitative approach with a sample of 100 respondents. Data collection was carried out using a questionnaire and data analysis using IBM SPSS Version 26. The results showed that social media influencers and emotional value directly had a positive and significant effect on purchasing decisions for virtual items in the Valorant online game. This means that the higher the social media influencer and emotional value, the more purchasing decisions will increase.